2007
DOI: 10.1007/s00381-007-0457-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of spasticity in children: comparison of selective dorsal rhizotomy and intrathecal baclofen pump implantation

Abstract: For children with moderate to severe spasticity, SDR and ITBP are both effective surgical treatments. Our results indicate SDR is more effective in reducing the degree of spasticity and improving function than ITBP is in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…Worse gross motor function is correlated with poorer outcome (6,7). Nevertheless, where spasticity has been shown by careful examination to confer a significant impediment to their motor progress, children with worse gross motor function still improve once their spasticity has been reduced by SDR (25).…”
Section: Outcome Of Sdrmentioning
confidence: 99%
“…Worse gross motor function is correlated with poorer outcome (6,7). Nevertheless, where spasticity has been shown by careful examination to confer a significant impediment to their motor progress, children with worse gross motor function still improve once their spasticity has been reduced by SDR (25).…”
Section: Outcome Of Sdrmentioning
confidence: 99%
“…4,7,9,18 Three randomized controlled trials and other nonrandomized prospective studies have provided strong evidence that SDR decreases lower-extremity spasticity in children with spastic diplegia. 4,17 Additional studies have demonstrated maintenance of the postoperative benefits in the long term.…”
Section: Selective Dorsal Rhizotomymentioning
confidence: 99%
“…Because baclofen crosses the blood-brain barrier poorly, this route optimizes the concentration of baclofen in the spinal cord while minimizing the systemic side effects. 7 However, intrathecal infusion has been linked to tolerance, requires surgical intervention for initial placement followed by pump replacements when the generator lifespan has been exceeded, involves routine pump refills, and has the possibility of infection with each intervention.…”
mentioning
confidence: 99%
“…16 Clinical studies have demonstrated that SDR results in short-and long-term improvement in lower-extremity tone and can lead to improved mobility, improved lower-limb function, decreased need for orthopedic surgical interventions, and an increased level of self-care for children with spastic diplegia and spastic quadriplegia. 2,5,7,8,10,12,15,18,19 Although nerve rootlet transection is limited to the lumbosacral rootlets in SDR, early anecdotal reports in the 1980s suggested the unexpected observation of improvements above the level of the lower extremities, termed "suprasegmental effects." Over the next decade, a number of small case series emerged describing improvement in upper-extremity function or tone following SDR, but only described qualitative improvement or quantitative improvement in select upper-extremity muscle groups.…”
Section: ©Aans 2013mentioning
confidence: 99%